Operational performance of the primary transport telecommunication network of Ukraine - Bondarenko, O. V.; Kostik, B. Ya.; Stepanov, D. N.; Levenberg, E. V. (Technology and design in electronic equipment, 2013)
The paper presents statistical data on the number, nature and causes of the damage to underground fiber-optic communication lines, on which the transport telecommunication primary network is based, using an example of Donetsk and Lugansk regions for the period between 2001 and 2010. Comparison of these characteristics with the values of similar parameters over 2001–2005 allows developing recommendations for the improvement of the reliability of telecommunication networks.